TET2 mutations are associated with specific 5-methylcytosine and 5-hydroxymethylcytosine profiles in patients with chronic myelomonocytic leukemia - Pérez, C; Martínez-Calle, N; Martín-Subero, J; Segura, V; Delabesse, E; Fernandez-Mercado, M; Garate, L; Alvarez, S; Rifon, J; Varea, S; Boultwood, J; Wainscoat, J; et al. (Public Library of Science, 2012)
Chronic myelomonocytic leukemia (CMML) has recently been associated with a high incidence of diverse mutations in genes such as TET2 or EZH2 that are implicated in epigenetic mechanisms. We have performed genome-wide DNA methylation arrays and mutational analysis of TET2, IDH1, IDH2, EZH2 and JAK2 in a group of 24 patients with CMML. 249 genes were differentially methylated between CMML patients and controls. Using Ingenuity pathway analysis, we identified enrichment in a gene network centered around PLC, JNK and ERK suggesting that these pathways, whose deregulation has beenrecently described in CMML, are affected by epigenetic mechanisms. Mutations of TET2, JAK2 and EZH2 were found in 15 patients (65%), 4 patients (17%) and 1 patient (4%) respectively while no mutations in the IDH1 and IDH2 genes were identified. Interestingly, patients with wild type TET2 clustered separately from patients with TET2 mutations, showed a higher degree of hypermethylation and were associated with higher risk karyotypes. Our results demonstrate the presence of aberrant DNA methylation in CMML and identifies TET2 mutant CMML as a biologically distinct disease subtype with a different epigenetic profile.